Two tales of one crash: Intergovernmental media relations and agenda building during the Smolensk airplane crash. (March 2021) - Myslik, Barbara; Khalitova, Liudmila; Zhang, Tianduo; Tarasevich, Sophia; Kiousis, Spiro; Mohr, Tiffany; Kim, Ji Young; Turska-Kawa, Agnieszka; Carroll, Craig; Golan, Guy
This study aims to advance the theoretical and practical knowledge of political public relations, and influence that political profile of the media can have on the agenda-building process. The influences of agenda indexing are also discussed with regard to different media profiles. A quantitative content analysis was conducted to examine the influence of Polish and Russian government messages from presidents and prime ministers regarding the Smolensk plane crash on media coverage in both counties. Newspapers were categorized by political profile representing pro-government, mainstream, or opposition profile. Nearly all of the hypotheses were fully supported for the first, second, and third level of agenda building. Results of this study demonstrate that political public relations' success and agenda indexing can be affected by a medium's political profile, particularly in the case of opposition media. Theoretical and practical implications are discussed along with areas of future research.